Dietary Interventions in Patients With Non-alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis - Houttu, Veera; Csader, Susanne; Nieuwdorp, Max; Holleboom, Adriaan G.; Schwab, Ursula (Frontiers in Nutrition, 2021)
Background: With no approved pharmacotherapy to date, the present therapeutic cornerstone for non-alcoholic fatty liver diseases (NAFLD) is lifestyle intervention. Guidelines endorse weight loss through dietary modifications, physical exercise or both. However, no consensus exists on the optimal dietary treatment. Objectives: The aim of our systematic review and meta-analysis was to summarize and assess the evidence for applied types of dietary interventions on liver and metabolic outcomes in patients with NAFLD, aside from any effects of exercise intervention. Methods: This systematic review was conducted according to Preferred Reporting Items of Systematic Reviews and Meta-analysis (PRISMA) statement guideline. The search was conducted in PubMed, Scopus and Cochrane databases in February 2020. Included were only dietary interventions without exercise. This study was registered at PROSPERO: CRD42020203573. Results: Eight randomized controlled trials, seven with endpoint reduction of hepatic steatosis, one with an assessment of endpoint fibrosis, were included in this systematic review, five of which were included in the meta-analysis. Mediterranean dietary interventions without energy restriction (n = 3) showed significant reduction of intrahepatic lipid content (IHL) (SDM: -0.57, 95% CI: -1.04, -0.10), but no significant change in alanine transaminase (ALT) (SDM: 0.59, 95% CI: -0.5, -1.68). Hypocaloric dietary interventions with foods high in unsaturated fatty acids (n = 2) led to a significant decrease in ALT (SDM: -1.09, 95% CI: -1.49, -0.69) and AST (SDM: -0.75, 95% CI: -1.27, 0.23) yet effects on steatosis could not be aggregated due to different assessment techniques. Mediterranean diet did not lead to significant changes in concentrations of gamma-glutamyl transpeptidase, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglyceride, fasting glucose or insulin, or homeostatic assessment for insulin resistance. Conclusions: In patients with NAFLD, Mediterranean and hypocaloric dietary interventions favoring unsaturated fatty acids result in improvements in IHL and transaminases. Because many dietary intervention studies are combined with exercise interventions and there is a paucity of amply sized studies examining dietary interventions on the more advanced and clinically relevant stages of NAFLD, i.e. active and fibrotic NASH, with multiparametric imaging and liver histology as outcome measures, the optimal dietary invention in NAFLD remains to be defined.